2012
DOI: 10.1016/j.taap.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of chlorine-induced lung injury by the type 4 phosphodiesterase inhibitor rolipram

Abstract: Chlorine is a highly toxic respiratory irritant that when inhaled causes epithelial cell injury, alveolar-capillary barrier disruption, airway hyperreactivity, inflammation, and pulmonary edema. Chlorine is considered a chemical threat agent, and its release through accidental or intentional means has the potential to result in mass casualties from acute lung injury. The type 4 phosphodiesterase inhibitor rolipram was investigated as a rescue treatment for chlorine-induced lung injury. Rolipram inhibits degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…Neutrophil deficiency/dysfunction is the hallmark predisposing factor for the development of invasive fungal infection caused by A. fumigatus (6,24). However, recruitment of neutrophils to the lung is a hallmark of Cl 2 gas exposure (16,57,71). Indeed, we observed that Cl 2 -exposed mice challenged with A. fumigatus had much higher neutrophil levels than either air-exposed mice challenged with A. fumigatus or mice exposed to Cl 2 alone.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Neutrophil deficiency/dysfunction is the hallmark predisposing factor for the development of invasive fungal infection caused by A. fumigatus (6,24). However, recruitment of neutrophils to the lung is a hallmark of Cl 2 gas exposure (16,57,71). Indeed, we observed that Cl 2 -exposed mice challenged with A. fumigatus had much higher neutrophil levels than either air-exposed mice challenged with A. fumigatus or mice exposed to Cl 2 alone.…”
Section: Discussionmentioning
confidence: 67%
“…It would be important in future studies to determine the extent by which Cl 2 affects assembly of the NADPH oxidase complex in neutrophils. Although neutrophils are often documented to be part of the lung response to Cl 2 gas exposure, and thus deemed a harmful contributor to lung injury, experimental studies have shown that some therapeutic interventions after Cl 2 exposure may ameliorate lung injury and/or lung function without having a significant impact on neutrophil numbers (16,52,67). This would suggest that some aspects of Cl 2 -induced lung injury are not mediated by neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The promotion of cAMP in ALI inhibited edema, inflammation, and hyperreactivity [40]. The effects of phosphatiosomes on pulmonary edema and neutrophil infiltration were thought to be related to the stimulation of cAMP.…”
Section: Discussionmentioning
confidence: 97%
“…Pulmonary function and airway reactivity to methacholine were measured by forced oscillation by using a FlexiVent system (SCIREQ, Montreal, Quebec, Canada) as described (5,13).…”
Section: Methodsmentioning
confidence: 99%